1991
DOI: 10.1111/j.1439-0434.1991.tb00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen and Phosphorus on the Growth of Microorganisms Associated with Apple Replant Disease and on Apple Seedlings Grown in Soil Infested with these Microorganisms*

Abstract: The growth of fungi causing apple replant disease (ARD) was inhibited by the addition of N and P to the growing medium. The population of bacteria antagonistic to ARD‐causing fungi was significantly increased in the growing medium supplemented with N 400 P 400 mg/l or greater. The application of nitrogen alone or in combination with phosphorus to soil infested with fungi or bacteria that cause apple replant disease significantly increased seedling height. The addition of P alone to these infested soils did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 5 publications
2
10
0
Order By: Relevance
“…3− for specific adsorption sites on the solid surface to reduce the adsorption of soil P. 28 In addition, PFA can form soil humic matter clay mineral complexes, thereby reducing P fixation. Since P is an important influencing and limiting factor in ARD control, 36 it is speculated that PFA may activate the soil P in the long-term process, thus alleviating the ARD to a certain extent.…”
Section: Resultsmentioning
confidence: 99%
“…3− for specific adsorption sites on the solid surface to reduce the adsorption of soil P. 28 In addition, PFA can form soil humic matter clay mineral complexes, thereby reducing P fixation. Since P is an important influencing and limiting factor in ARD control, 36 it is speculated that PFA may activate the soil P in the long-term process, thus alleviating the ARD to a certain extent.…”
Section: Resultsmentioning
confidence: 99%
“…Increased initial root length is a known consequence of high P supply to wild cherry (Neilsen et al, 1990b). Neilsen et al (1989) also demonstrated that P likely increased initial diameter growth and the first 2 years of yield of McIntosh and Delicious apple trees irrigated with wastewater high in P. Increase in tree growth and fruit set by the application of monoammonium phosphate could also be because of its deleterious effect on replant causing fungi or bacteria and promotion of antagonistic bacteria in soil (Utkhede and Smith, 1991;Utkhede and Li, 1989b). Neilsen et al (1989) also demonstrated that P likely increased initial diameter growth and the first 2 years of yield of McIntosh and Delicious apple trees irrigated with wastewater high in P. Increase in tree growth and fruit set by the application of monoammonium phosphate could also be because of its deleterious effect on replant causing fungi or bacteria and promotion of antagonistic bacteria in soil (Utkhede and Smith, 1991;Utkhede and Li, 1989b).…”
Section: Discussionmentioning
confidence: 99%
“…Application of high rates of P in the year of planting increased the number of flower clusters and fruit set in sub-sequent years (Neilsen et al, 1990a). Recently it was shown that application of N, with or without P, to apple-replant-problem-soils suppresses the growth of replant-disease causing fungi or bacteria and promotes growth of antagonistic bacteria in soil (Utkhede and Smith, 1991). Fertilization of replant soil with monoammonium phosphate (llN:55P:0K) reversed the stunting effect caused by replant-causing bacterial isolates under greenhouse conditions (Utkhede and Li, 1989b).…”
Section: Introductionmentioning
confidence: 99%
“…Moharana et al found that phosphate fertilizer can improve the soil environment and increase soil enzyme activity. The application of a certain amount of phosphate fertilizer in orchards can effectively control the occurrence of apple replant disease or reduce the degree of damage that it induces . Hao and Xiao showed that adding superphosphate to replant soil can promote the growth of medicinal materials and alleviate replanting obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…The application of a certain amount of phosphate fertilizer in orchards can effectively control the occurrence of apple replant disease or reduce the degree of damage that it induces. 12 Hao and Xiao 13 showed that adding superphosphate to replant soil can promote the growth of medicinal materials and alleviate replanting obstacles. The application of quicklime has been shown to improve the stability of soil aggregates 14 and reduce the occurrence of soilborne diseases of strawberries grown in greenhouse conditions.…”
Section: Introductionmentioning
confidence: 99%